The Influence of Influencer Marketing and Brand Awareness on Purchase Decisions of Scarlett Products Among Female Students of the Business Administration Study Program at the College of Administrative Sciences Bengkulu - Muhammad Bima Eka Putra; Azuwandri (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to determine the influence of influencer marketing and brand awareness on the purchase decisions of Scarlett products among female students of the Business Administration Study Program at the College of Administrative Sciences Bengkulu, both partially and simultaneously. Several factors are discussed in this research, including influencer marketing and brand awareness. The research subjects are 102 female students from the Business Administration Program at STIA Bengkulu. In this study, the researcher used data collection methods such as observation and questionnaire distribution. The data analysis techniques used include instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and the coefficient of determination analysis. The results show that influencer marketing has a positive effect on purchase decisions, and brand awareness also has a positive effect on purchase decisions. Therefore, it can be concluded that influencer marketing and brand awareness have both partial and simultaneous effects on the purchase decisions of Scarlett products among female students of the Business Administration Study Program at the College of Administrative Sciences Bengkulu.